The Influence of Rewards and Career Development on Employee Job Satisfaction at the Aceh Personnel Agency: The Mediating Role of Organizational Commitmen - Naufal'alim, Muhammad; Faisal; Harmen, Hamdi (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aims to analyze the influence of rewards and career development on employee job satisfaction at the aceh personnel agency: the mediating role of organizational commitmen. This research applies an individual-level analysis, involving a population and sample comprising 143 employees of the Aceh Personnel Agency. The data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The findings reveal that rewards have a positive and significant effect on employee job satisfaction at the Aceh Personnel Agency. Similarly, career development also has a positive and significant effect on job satisfaction. In addition, rewards and career development both have a positive and significant impact on organizational commitment. Furthermore, organizational commitment positively and significantly influences employee job satisfaction. The study also finds that organizational commitment significantly mediates the relationship between rewards and job satisfaction, as well as between career development and job satisfaction.